2012
DOI: 10.1590/s1415-47572012005000059
|View full text |Cite
|
Sign up to set email alerts
|

Identification of RAPD and SCAR markers associated with yield traits in the Indian tropical tasar silkworm Antheraea mylitta drury

Abstract: The tropical tasar silkworm, Antheraea mylitta, is a semi-domesticated vanya silk-producing insect of high economic importance. To date, no molecular marker associated with cocoon and shell weights has been identified in this species. In this report, we identified a randomly amplified polymorphic DNA (RAPD) marker and examined its inheritance, and also developed a stable diagnostic sequence-characterized amplified region (SCAR) marker. Silkworms were divided into groups with high (HCSW) and low (LCSW) cocoon a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…In a previous study, Su et al (2007) developed a 'strain-specific' G. lucidum ISSR-based SCAR marker, which could identify certain strains of G. lucidum, but it was not a species-specific marker. RAPD-SCAR markers have been successfully developed for the identification of some other organisms, including plants, animals, and microbes (Jiang et al, 2009;Dutta et al, 2012;Lee et al, 2013;Yang et al, 2013, Fu et al, 2015Zhang et al, 2015;Mei et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Su et al (2007) developed a 'strain-specific' G. lucidum ISSR-based SCAR marker, which could identify certain strains of G. lucidum, but it was not a species-specific marker. RAPD-SCAR markers have been successfully developed for the identification of some other organisms, including plants, animals, and microbes (Jiang et al, 2009;Dutta et al, 2012;Lee et al, 2013;Yang et al, 2013, Fu et al, 2015Zhang et al, 2015;Mei et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…According to the best of our knowledge, this is the first RAPD-SCAR study on L. japonica identification. However, some studies have reported the RAPD-SCAR technique for the identification and authentication of other organisms like pepper (Jiang, Jianhua, & Li, 2009), longan fruits (Yang et al, 2013), shrimp (Dutta et al, 2014), silkworm (Dutta et al, 2012), microbes (Lee, Lee, Lee & Lee, 2013) among others.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the features of long sequence and high annealing temperature ensure that ISSR-PCR would exhibit high stability and reproducibility (Nagaoka & Ogihara, 1997;Tsumura et al, 1996;Qian et al, 2001;Naik et al, 2017). Although ISSR is widely used in studies on various plants (Qian et al, 2001;Cao et al, 2006;Tanya et al, 2011), fungi (Menzies et al, 2003) and some insects Dutta et al, 2012;Barbosa et al, 2014), but it was less used on the study of termites (Long et al, 2009).…”
Section: Introductionmentioning
confidence: 99%